2013
DOI: 10.1016/s1001-6279(13)60014-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of bend scour with an air-bubble screen – morphology and flow patterns

Abstract: The interplay between streamwise flow, curvature-induced secondary flow, sediment transport and bed morphology leads to the formation of a typical bar-pool bed morphology in open-channel bends. The associated scour at the outer bank and deposition at the inner bank may endanger the outer bank's stability or reduce the navigable width of the channel. Previous preliminary laboratory experiments in a sharply curved flume with a fixed horizontal bed have shown that a bubble screen located near the outer bank can g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
1
10
2
Order By: Relevance
“…For the rectangular channel, Blanckaert et al (2010) suggest that scouring close to the wall could be reduced with increasing wall roughness, whereas for the trapezoidal channel, depth-averaged downstream velocity over the bank toe is similar for all experiments regardless of the outer-bank roughness. Recently, in the very same laboratory installation, Dugué et al (2013) proposed a solution based on the installation of a bubble screen to reduce bend scour.…”
Section: Introductionmentioning
confidence: 99%
“…For the rectangular channel, Blanckaert et al (2010) suggest that scouring close to the wall could be reduced with increasing wall roughness, whereas for the trapezoidal channel, depth-averaged downstream velocity over the bank toe is similar for all experiments regardless of the outer-bank roughness. Recently, in the very same laboratory installation, Dugué et al (2013) proposed a solution based on the installation of a bubble screen to reduce bend scour.…”
Section: Introductionmentioning
confidence: 99%
“…Blanckaert et al (2008) have shown that the bubble-induced secondary flow causes redistribution of the longitudinal velocity and of the boundary shear stress, which suggests that the bubble screen would also lead to morphological redistribution in configurations with mobile riverbed. Dugué et al (2013) have performed experiments under one hydraulic condition in the same curved laboratory flume as Blanckaert et al (2008). Instead of fixing a horizontal bed, Dugué et al (2013) performed experiments under clear-water scour conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Dugué et al (2013) have performed experiments under one hydraulic condition in the same curved laboratory flume as Blanckaert et al (2008). Instead of fixing a horizontal bed, Dugué et al (2013) performed experiments under clear-water scour conditions. Under clear-water scour conditions, no sediment is fed to the flume and the critical shear stress necessary for transporting sediment is not exceeded in the straight inflow reach of the flume.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations